Associations of patient-centered medical home with quality of care, patient experience, and health expenditures: A STROBE-compliant cross-sectional study. Issue 21 (28th May 2021) - Xie, Zhigang; Yadav, Sandhya; Larson, Samantha A.; Mainous, Arch G.; Hong, Young-Rock
Abstract : Abstract: In efforts to improve the delivery of quality primary care, patient-centered medical home (PCMH) model has been promoted. However, evidence on its association with health outcomes has been mixed. The aim of this study was to assess the performance of PCMH model on quality of care, patient experience, health expenditures. This was a cross-sectional study of the 2015–2016 Medical Expenditure Panel Survey-Medical Organization Survey linked data, including 5748 patient-provider pairs. We examined twenty-four quality of care measures (18 high-value and 6 low-value care services), health service utilization, patient experience (patient-provider communication, satisfaction), and health expenditure. Of 5748 patients, representing a weighted population of 56.2 million American adults aged 18 years and older, 44.2% were cared for by PCMH certified providers. 9.3% of those with PCMHs had at least one inpatient stay in the past year, which was comparable to the 11.4% among those with non-PCMHs. Similarly, 17.4% of respondents cared for by PCMH and 18.5% cared for by non-PCMH had at least one ED visit. Overall, we found no significant differences in quality of care measures (neither high-nor low-value of care) between the two groups. The overall satisfaction, the experience of access to care, and communication with providers were also comparable. Patients who were cared for by PCMHs had less total health expenditure (difference 217) and out-of-pocket spending (difference 91) than those cared for by non-PCMHs; however, none of these differences reached the statistical significance (adjusted P > 0.05 for all). This study found no meaningful difference in quality of care, patient experience, health care utilization, or health care expenditures between respondents cared for by PCMH and non-PCMH. Our findings suggest that the PCMH model is not superior in the quality of care delivered to non-PCMH providers. Abstract : Supplemental Digital Content is available in the text